Rare nervous system involvement in an anti-myelin oligodendrocyte-positive case: spinal leptomeningeal involvement - Tuğan Yıldız, Buket; Tuncel, Deniz; Yurttutan, Nursel; Çöklü, Şerife (Journal of Surgery and Medicine, 2022)
Anti-myelin oligodendrocyte (MOG)-positive cases have a variable clinical presentation. MOG autoantibodies are associated with acute disseminated encephalomyelitis, multiple sclerosis, clinically isolated syndrome, neuromyelitis optica, isolated optic neuritis, and transverse myelitis. Our patient had bilateral optic neuritis with acute tetraparesis. Cranial magnetic resonance imaging (MRI) showed leptomeningeal contrast involvement and contrast enhancement in all cranial nerve nuclei. Spinal MRI revealed leptomeningeal contrast enhancement, and a contrast-enhancing lesion was found in the cervical spinal cord. This case is worth presenting because spinal leptomeningeal involvement is rare in anti-MOG-positive patients.